A novel mutation in HSD11B2 causes apparent mineralocorticoid excess in an Omani kindred. Issue 1 (15th August 2016) - Yau, Mabel; Azkawi, Hanan Said Al; Haider, Shozeb; Khattab, Ahmed; Badi, Maryam Al; Abdullah, Wafa; Senani, Aisha Al; Wilson, Robert C.; Yuen, Tony; Zaidi, Mone; New, Maria I.
Abstract : Apparent mineralocorticoid excess (AME) is a rare autosomal recessive genetic disorder causing severe hypertension in childhood due to a deficiency of 11β‐hydroxysteroid dehydrogenase type 2 (11βHSD2), which is encoded by HSD11B2 . Without treatment, chronic hypertension leads to early development of end‐organ damage. Approximately 40 causative mutations in HSD11B2 have been identified in ∼100 AME patients worldwide. We have studied the clinical presentation, biochemical parameters, and molecular genetics in six patients from a consanguineous Omani family with AME. DNA sequence analysis of affected members of this family revealed homozygous c.799A>G mutations within exon 4 of HSD11B2, corresponding to a p.T267A mutation of 11βHSD2. The structural change and predicted consequences owing to the p.T267A mutation have been modeled in silico . We conclude that this novel mutation is responsible for AME in this family.